New Markov-Chain Monte Carlo analyses for the evaluation of the antiproton background. (December 2020) - De la Torre Luque, P; Gargano, F; Loparco, F; Mazziotta, M N; Serini, D
Abstract: Current measurements of the cosmic ray spectra have reached unprecedented accuracy thanks to the new generation of experiments, and in particular the AMS-02 mission. At the same time, significant progress has been made in the propagation models of galactic cosmic rays. Nevertheless, the current knowledge on spallation cross sections is very poor, impeding a more precise estimation of the diffusion coefficient. In this work we show a new Markov-Chain Monte Carlo algorithm able to derive the propagation parameters from the flux ratios of light secondary cosmic rays (Li, Be, B) to C and O and a new procedure able to combine the flux of these secondary cosmic rays in order to get rid of the uncertainties associated to their production cross sections. Then, we show that the antiproton spectrum inferred from this diffusion model match experimental data much better than with earlier analyses, discarding the excess of data previously explained as a possible signature of antiproton production from dark matter.